ব্রিক লেন: বিলেতের বাঙালিটোলা - রহমান, ঊর্মি (ঢাকা : সাহিত্য প্রকাশ, 1993)
On the socioeconomic conditions of the Bengalis and immigrated settled in London since 1960.
In Bengali.
Keywords: Bangladesh -- Social conditions; Bangladesh -- Economic conditions